Peningkatan Kapasitas Penghuni Pondok Pesantren dalam Pencegahan Food Borne Disease dengan Metode Peer Education - Nur Siyam; Widya Hary Cahyati (VISIKES: Jurnal Kesehatan Masyarakat, 2018)
The outbreaks of food poisoning in 2015 occurred in several districts, namely Batang, Langkat, Kebumen, Tabanan and Kolako districts. Preliminary study on 20 female Pesantren Pondok Pesantren "Takhfidzul Quran Miftahul Ulum" Terboyo Wetan, 14% have ever had diarrhea or abdominal pain in the last 3 months. For the provision of food in this boarding school, held a cooking system, then eat together. So if the processing and storage of food less hygienic, can increase the risk of food borne disease. Therefore, efforts should be made to increase the capacity of boarding school dwellers in preventing food borne disease, so the health of the boarding school residents can be maintained. Implementation of foodborne diseases prevention training with peer education method begins with licensing and coordination with pesantren boarding school, socialization, increasing knowledge of disease hazard, prevention of foodborne diseases, healthy food, preparation of hygiene food processing and storage form, direct practice of processing And food storage in Pondok Pesantren, the process of measuring the results of dedication and data processing, and evaluation and dissemination of community service activities. The data collection instrument is a questionnaire for measuring knowledge, attitude and practice. Research subjects consist of administrators, teachers/ ustad and ustadzah and santri. Communication, information and education provided by involving the discussion of cottage and boardingers of pesantren. Test the results data with Wilcoxon.The results show the knowledge, attitude, and behavior of prevention of foodborne diseases after being given foodborne diseases prevention training with peer education method significantly increased p value <0.05. Successive, knowledge p = 0,000, attitude p = 0.005 and preventive behavior p = 0.005.The outbreaks of food poisoning in 2015 occurred in several districts, namely Batang, Langkat, Kebumen, Tabanan and Kolako districts. Preliminary study on 20 female Pesantren Pondok Pesantren "Takhfidzul Quran Miftahul Ulum" Terboyo Wetan, 14% have ever had diarrhea or abdominal pain in the last 3 months. For the provision of food in this boarding school, held a cooking system, then eat together. So if the processing and storage of food less hygienic, can increase the risk of food borne disease. Therefore, efforts should be made to increase the capacity of boarding school dwellers in preventing food borne disease, so the health of the boarding school residents can be maintained. Implementation of foodborne diseases prevention training with peer education method begins with licensing and coordination with pesantren boarding school, socialization, increasing knowledge of disease hazard, prevention of foodborne diseases, healthy food, preparation of hygiene food processing and storage form, direct practice of processing And food storage in Pondok Pesantren, the process of measuring the results of dedication and data processing, and evaluation and dissemination of community service activities. The data collection instrument is a questionnaire for measuring knowledge, attitude and practice. Research subjects consist of administrators, teachers/ ustad and ustadzah and santri. Communication, information and education provided by involving the discussion of cottage and boardingers of pesantren. Test the results data with Wilcoxon.The results show the knowledge, attitude, and behavior of prevention of foodborne diseases after being given foodborne diseases prevention training with peer education method significantly increased p value <0.05. Successive, knowledge p = 0,000, attitude p = 0.005 and preventive behavior p = 0.005.